MASTER OF MEDIEVAL ARCHAEOLOGY-PROFESSOR MADIYAR ELEUOV (75TH ANNIVERSARY) (Journal of history, 2021)
The famous archaeologist and famous teacher – doctor of historical sciences, professor Madiyar Eleuov turned 75 years old this year. The life path of a scientist who has devoted his life to the science of archaeology is an example for young people and an example for the younger generation.